Development of Online Alfalfa Management Extension Education Resources Amid the COVID-19 Pandemic. (7th May 2021) - da Silva, Liliane Severino; Mullenix, Kim K; Dillard, S Leanne L; Tucker, Jennifer J; Thompson, Gerry
Abstract: Prior to the COVID-19 pandemic, many Extension programs used web-based resources but balanced those with in-person events for interpersonal connection with producers and for individuals with limited access to technology. In 2020, in-person Extension programs were cancelled or converted to online versions. This was the case for the 'Alfalfa in the South' (AITS) program, a collaboration between Auburn University (AU) and University of Georgia (UGA). Two online AITS programs were held (May and Sept) and are examples of rethinking traditional models and optimizing resources to prioritize our commitment to clientele. In its first program, the program content was delivered through 1) a series of webinars from AU, UGA and University of Florida (UF) Extension Specialists (n = 6 webinars) and a 1-h live roundtable discussion held through Zoom on May 13, 2020. The roundtable consisted of a moderator interacting with five panelists (faculty, Extension agents and producers) answering live questions from the audience (n = 45 participants). All content was archived by the Alabama Cooperative Extension System (ACES) for later access using online resources. The second program occurred in Sept 2020 as a collaboration between AU, UF and UGA Specialists. This program included several pre-recorded short videos and e-publications on topics in establishment and management of alfalfa in the South. In 2020, the web-metrics gathered for the ACES webpage and Youtube channel across these programs sums over 3000 views of alfalfa resources. Similarly, engagement on the AL Beef and Forage Extension Facebook pages were over 3000 people. Although a traditional formal post-programming survey was not conducted with participants, an online survey was distributed simultaneously in the south region (n = 12 states) from May through December 2020 aiming to identify main challenges and limitations of alfalfa adoption. The results (n = 212 respondents) showed approximately 65% participants already invested time in learning about alfalfa using Extension online programs and resources available. This shows increased importance of online outreach as a tool to maintain relevance and connection with clientele.